Women's Rights In The Division Of Customary Inheritance Rote Ndao Nusa Tenggara Timur (Supreme Court Decision No.1048 K/Pdt/2012) - Febrina Indrasari (International Journal of Education, Vocational and Social Science, 2023)
This research aims to answer the legal construction of women's rights in the inheritance of Rote Ndao East Nusa Tenggara custom, and analysis of Supreme Court Decision Number 1048 K/Pdt/2012 in the distribution of women's inheritance in Rote Ndao East Nusa Tenggara custom. This research uses a doctrinal approach, using the Legislation approach, case approach and concept approach. Rote Ndao Regency of East Nusa Tenggara Province is included in the patrilineal group, which means that sons become or are recognized as heirs and daughters do not have the right position as heirs because in this case girls are not included in the patrilineal group, legal construction related to the recognition of women's rights is reflected in Supreme Court Decision Number 1048 K / Pdt / 2012 which provides a concrete picture related to the recognition of women's rights in customary inheritance law, especially in Rote Ndao Regency of East Nusa Tenggara Province. The attitude of the Supreme Court Judges who reformed the inheritance law of Rote Ndao by recognizing women's rights in the distribution of inheritance in accordance with the Ratio Decidendi states that customary laws that are not in accordance with legal developments in society, such as customary laws that do not recognize women's rights as equal to the position of men, can no longer be maintained.